(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The field experiment was conducted at Mahmudkati, Monirampur under Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Jashore for two consecutive years of 2021-22 and 2022-23 through inclusion of mustard var. BARI Sarisha-14 in the fallow period and to study the comparative agronomic performance economic return, increasing cropping intensity, productivity and land use efficiency. The experiment was laid out in a randomized complete block design (RCBD) with ten dispersed replications. Three crops pattern (T. Aman rice –Mustard - Boro rice) and farmers’ existing pattern (T.Aman- fallow- Boro) as control were tested.Two years mean data showed that the improved management practices provided higher yield in improved pattern. Average higher rice equivalent yield (REY), (20.22 t ha-1) production efficiency (59.92 kg ha-1 day-1) and 92.88% land utilization indexwas found in the improved cropping pattern in both years. Gross return of the improved pattern was Tk..711010 ha-1 which was more than 68.24% higher than farmer’s pattern of Tk. 422615 ha-1. Gross margin (Tk. 483610 ha-1) and MBCR (2.13) were also higher in improved cropping pattern in both years than existing pattern. Bangladesh J. Agril. Res. 48(1): 125-136, March 2023